From Habermas’ Bourgeois Public Sphere to Gerbaudo’s Online Crowds: A Foucauldian Discourse Analysis of Kenya’s #EngageThePresident on X Space - Muya, Paul; Otiende, Josephine (International Journal of Communication and Public Relation, 2025)
Purpose: The main purpose of this paper is to examine the discourse of governance, bio-power and political accountability in Kenya. Applying the lens of Foucauldian discourse analysis, the study explores #EngageThePresident X Space. At this forum, President Ruto and Gen Z participants engaged in a discussion at the height of the 2024 anti-tax law protests in Kenya. Methodology: Underpinned by public sphere theory, we first examine the construction of subjects' positions and power relations within the discourse. Second, we analyse discourses surrounding governance, political accountability and bio-power in Kenya. Third, we explore how language, institutions, and cultural norms influence the production of knowledge, categorisation of individuals, and construction of contextual truths. Findings: The study found that Gen Z emerged in the discourse as a fragmented subject, ranging from patriotic and emotionally volatile to naïve and tech-savvy citizens. President Ruto was constructed with multiple conflicting subject positions, demonstrating a dynamic nature of political fashioning in a legitimacy crisis. In addition, while the President tried to reassert control through a package of consultative governance, Gen Z’s fragmented discourse infused the state narrative with grief, rage, irony and resistance. Kenya’s #EngageThePresident represents a reconfiguration of the public sphere in the digital age, one where collective emotion, decentralised participation and real-time responsiveness redefine governance discourse.Unique Contribution to Theory, Practice and Policy: The study contributes to the practice of Foucauldian discourse analysis by examining the accelerated pace of digital narratives in digital media in the Global South. It highlights a broader democratic recalibration in which citizens are not passive recipients of state narratives but active co-authors of the nation’s political discourse and statecraft. The study recommends that entrenching platformised engagement between political leaders and subaltern citizens has the potential to catalyse political stability for the maturing nations in the Global South. Future research on the impact of Gen Z awakening on the political destiny of President Ruto is deemed necessary.
Journal article
Keywords: Social Media; Public Sphere; Discursive Governance; Political Accountability; Gen Z